2004
DOI: 10.1017/s1367943004001301
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive genotyping of the endangered Apennine brown bear: a case study not to let one's hair down

Abstract: Individual identification was assessed for 30 brown bears (Ursus arctos) from the endangered Apennine population in central Italy, mostly through non-invasive sampling. Shed hairs were used as a source of DNA to obtain single genotype profiling at 12 microsatellite loci. Average expected heterozygosity (0.438) and mean number of alleles per locus (2.2) showed that the level of genetic diversity was one of the lowest recorded for brown bear populations across their European and North American ranges. A large po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 54 publications
0
50
0
1
Order By: Relevance
“…Knowledge of the species' taxonomic status and population genetic structure is fundamental to developing effective strategies to this end (Lorenzini et al, 2004). Inter-and intraspecific phylogenetic knowledge also would help clarify the species' biology, and would resolve appropriate conservation and management units for this species (An, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the species' taxonomic status and population genetic structure is fundamental to developing effective strategies to this end (Lorenzini et al, 2004). Inter-and intraspecific phylogenetic knowledge also would help clarify the species' biology, and would resolve appropriate conservation and management units for this species (An, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…After checking the concentration, the DNA was stored in a freezer at -20 °C. Five nuclear microsatellite loci were used (Røed and Midthjell 1998;Postma et al 2001;Lorenzini et al 2004): NVHRT30, NVHRT71, NVHRT48, NVHRT16 and NVHRT24 (further abbreviated as N30, N71, N48, N16 and N24). We used two multiplex reactions for PCR amplification -N30 and N71 as multiplex No 1, and N48, N16 and N24 as multiplex No 2.…”
Section: Dna Marker Analysismentioning
confidence: 99%
“…In 2004, we produced a preliminary, hair-snag based estimate of 43 bears (95% CI = 35-67) for this population, but low capture probability and limited power to model heterogeneity affected precision and reliability of the population estimate (Gervasi et al 2008). In addition, the low genetic variability of this population (Lorenzini et al 2004;Randi et al 1994) potentially reduces our power in distinguishing individual genotypes as observed in similar studies on brown bears (Paetkau 2004;Waits et al 2001), thus requiring an increased number of microsatellite loci.…”
Section: Introductionmentioning
confidence: 98%
“…The Apennine brown bear lives in a small and isolated population (Ciucci and Boitani 2008;Gervasi et al 2008), and is highly depleted of genetic variability (Lorenzini et al 2004;Randi et al 1994). In 2004, we produced a preliminary, hair-snag based estimate of 43 bears (95% CI = 35-67) for this population, but low capture probability and limited power to model heterogeneity affected precision and reliability of the population estimate (Gervasi et al 2008).…”
Section: Introductionmentioning
confidence: 99%